Evaluation of the relationship between lifestyle and body mass index in administrative employees of Bojnourd, Iran - Mohsen Saber Moghaddam Ranjbar (Journal of Nursing and Midwifery Sciences, 2015)
Background and Purpose: Lifestyle is defined as the unique behavioral patterns and habits of an individual. If lifestyle is unbalanced, risk of illnesses and burdensome events increases. Lifestyle plays a key role in the modulation of body mass index (BMI) and prevention of obesity. This study aimed to investigate the relationship between lifestyle and BMI in the administrative employees of Bojnourd. Iran in 2014. Materials and Methods: This cross-sectional study was conducted on 380 government employees selected by stratified random sampling with proportional allocation in each stratum. Data were collected using prepared checklists and lifestyle questionnaires. Weight and height of subjects were measured using standardized methods. Data analysis was performed using descriptive statistics and Pearson's correlation coefficient in SPSS V.18. Results: In this study, frequency of lifestyle was 4.58%, 52.48% and 42.94% in scoring scales of favorable, relatively favorable and unfavorable, respectively. Moreover, 6.6% of the subjects were underweight, 34.7% were normal, 36.1% were overweight, and 21.8% were obese. A significant correlation was observed between BMI and age (P=0.000), gender (P=0.03), physical exercise (P=0.04) and nutrition status (P=0.003) of the subjects. Conclusion: According to the results of this study, lack of physical activity and improper diet are the most important causes of obesity among administrative employees. Therefore, modification of lifestyle should be mandatory in order to improve BMI and overall health of these individuals.